Sceptical theism and the evil-god challenge - Hendricks, Perry (Religious studies, 2018)
This article is a response to Stephen Law's article The evil-god challenge'. In his article, Law argues that if belief in evil-god is unreasonable, then belief in good-god is unreasonable; that the antecedent is true; and hence so is the consequent. In this article, I show that Law's affirmation of the antecedent is predicated on the problem of good (i.e. the problem of whether an all-evil, all-powerful, and all-knowing God would allow there to be as much good in the world as there is), and argue that the problem of good fails. Thus, the antecedent is unmotivated, which renders the consequent unmotivated. Law's challenge for good-god theists is to show that good-god theism is not rendered unreasonable by the problem of evil in the same way that evil-god theism is rendered unreasonable by the problem of good. Insofar as the problem of good does not render belief in evil-god unreasonable, Law's challenge has been answered: since it is not unreasonable to believe in evil-god (at least for the reasons that Law gives) it is not unreasonable to believe in good-god. Finally, I show that - my criticism aside - the evil-god challenge turns out to be more complicated and controversial than it initially appears, for it relies on the (previously unacknowledged) contentious assumption that sceptical theism is false.